2023
DOI: 10.1039/d2tc05133h
|View full text |Cite
|
Sign up to set email alerts
|

Deep ultraviolet optical limiting materials: 2D Ti3C2 and Ti3AlC2 nanosheets

Abstract: This is the first demonstration of the OL effect in 2D materials below 290 nm, and shows the largest UV two-photon absorption cross-section of any 2D material available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…It is worth noting that although the 532 nm band is not the focus of this work based on the Z-scan data, the larger TPA coefficients (shown in Table ) of Nb 4 C 3 in the 532 nm band cannot be ignored. When the excitation wavelength is 355 nm and the laser pulse width is 18 ps, the TPA coefficients of Ti 3 AlC 2 and Ti 3 C 2 are 0.32 ± 0.01 and 0.20 ± 0.02 cm GW –1 , and the σ TPA values are 3.86 ± 0.06 × 10 –45 and 2.08 ± 0.02 × 10 –45 cm 4 s, respectively . Which are much smaller than those of Nb 4 C 3 (8.44 ± 0.08 cm GW –1 and 2.13 ± 0.02 × 10 –43 cm 4 s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that although the 532 nm band is not the focus of this work based on the Z-scan data, the larger TPA coefficients (shown in Table ) of Nb 4 C 3 in the 532 nm band cannot be ignored. When the excitation wavelength is 355 nm and the laser pulse width is 18 ps, the TPA coefficients of Ti 3 AlC 2 and Ti 3 C 2 are 0.32 ± 0.01 and 0.20 ± 0.02 cm GW –1 , and the σ TPA values are 3.86 ± 0.06 × 10 –45 and 2.08 ± 0.02 × 10 –45 cm 4 s, respectively . Which are much smaller than those of Nb 4 C 3 (8.44 ± 0.08 cm GW –1 and 2.13 ± 0.02 × 10 –43 cm 4 s).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of metal nanoparticles and semiconductors have been found to exhibit excellent OL responses to nanosecond laser pulses . Similarly, carbon nanomaterials such as carbon black suspensions and carbon nanotubes have been used for OL materials and other NLO applications. However, studies on the OL properties of the MXene family are fewer and mainly focused on the visible to SWIR wavelengths, and there are no reports on the OL properties of 2D Nb 4 AlC 3 and 2D Nb 4 C 3 too, as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…For pure nanosheets on excitation with ns light in the visible region, despite the gapless characteristics, two-photon absorption (TPA) is reported to be the primary NLO process of Ti 3 C 2 T x . 4,10 Given the appreciable linear absorption of Ti 3 C 2 T x at 532 nm, one-photon absorption (OPA) should exist as an ever-present process within the duration of the absorption behavior. Hence, a slope of 0.69 for MXene implies that both OPA and TPA occur when the sample is exposed to a 532 nm incident laser, and that TPA plays a predominant role, resulting in the RSA response.…”
Section: Nlo Propertiesmentioning
confidence: 99%
“…3 The chemical formula of MXenes can be expressed as M n+1 X n T x (n = 1, 2, or 3), where M represents n + 1 layers of early transition metal, X denotes carbon and/or nitrogen, and T stands for surface terminating groups such as -F, QO, and -OH. 3 Experimental studies have demonstrated the prominent nonlinear optical (NLO) properties of the MXene family, which holds great potential for modern photonics applications such as optical limiting (OL), 4,5 mode locking/Qswitching pulse generation, 6,7 optical computing, 8 sub-bandgap photodetection, 9 etc. As the first reported and most studied MXene, Ti 3 C 2 T x shows a broadband NLO response, with its saturation absorption (SA) and reverse saturation absorption (RSA) behaviors being explored by several research groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation